The Use of Collaborative Method through Jeopardy Games to Enhance Learners’ Vocabulary Knowledge - Sinaga, Melda Nofriyanti; Simanjuntak, Debora Chaterin (Journal of Language and Literature Studies, 2024)
Vocabulary knowledge is a primary aspect of understanding word meanings, including definition, nuances, and usage in different contexts. This research aims to explore the use of the Collaborative method through Jeopardy games in enhancing students’ vocabulary knowledge. This research is a quantitative study, utilizing a comparative research design. The research involved 8th graders as the respondents. The paired sample T-test was used to assess the effectiveness of the method. Based on the findings, the Jeopardy games used in conjunction with the collaborative method significantly enhanced students’ vocabulary knowledge. The implications of this research indicate that the combination of Jeopardy games and collaborative methods appears to have advantages in improving language skills and vocabulary retention, as perceived by a significant portion of students; wherein, 82% of students perceived vocabulary growth after using Jeopardy games in a collaborative method and 73% of students found Jeopardy games used with collaborative methods to be interesting. There has been a marked improvement in students’ vocabulary knowledge. Incorporating interactive and collaborative activities, such as Jeopardy games, into language learning provides students with opportunities to improve their learning experiences and outcomes.